2011
DOI: 10.3109/09638288.2010.532281
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of hip joint pain in children with severe cerebral palsy

Abstract: Extensive abduction exercises, hippotherapy and presence of degenerative cartilage lesions on the anterior part of femoral head may be considered risk factors for hip pain appearance in the dislocated hip of a child with severe spastic CP. Other associated factors are abduction exercise intensity, age, excessive femoral anteversion and size of degenerative cartilage lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…5 The frequency of pain in spastic hip disease remains controversial. In a series of 73 children, Jóźwiak et al 24 showed that 55% of children with spastic dislocation of the hip were in pain, and the incidence reported in the literature varied between 25% and 55%. [25][26][27][28][29] In our study, 40% of the children had pain.…”
Section: Discussionmentioning
confidence: 99%
“…5 The frequency of pain in spastic hip disease remains controversial. In a series of 73 children, Jóźwiak et al 24 showed that 55% of children with spastic dislocation of the hip were in pain, and the incidence reported in the literature varied between 25% and 55%. [25][26][27][28][29] In our study, 40% of the children had pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that in none of the focus groups participants were oriented to think about hip pain specifically, findings suggest a difference between the countries in the occurrence of such pain. Chronic pain in children with CP is often related to hip dislocations [44], which was pointed out in six of the South African statements, whereas in Sweden, it was not mentioned at all. In accordance with the clinical prognostic messages published by Novak [2], this difference can probably be explained by the systematic, preventive CPUP surveillance that was introduced in Sweden two decades ago and which, since 2005, has been designated as a National Quality…”
Section: Occurrence Of Pain In School Settingsmentioning
confidence: 99%
“…Self-report questionnaires are the most common method for collecting information about pain, and pain intensity is the most common domain assessed by clinicians and researchers (Jensen, 2011). Pain intensity measures that have been used in youths with physical disabilities include the Wong-Baker FACES Pain Rating Scale (FACES) (e.g., Ramchandren et al , 2014; Tüzün et al , 2010), the 0 – 10 Numerical Rating Scale (NRS-11) (e.g., Jóźwiak et al , 2011; Suokas et al , 2012; Tieleman et al , 2011), and the Visual Analogue Scale (VAS) (e.g., Vles et al , 2008; Wen et al , 2013). Another straightforward option for assessing pain intensity is the (categorical) Verbal Rating Scale (VRS), which asks the respondent to select the word or phrase from a list (e.g., None, Mild, Moderate, Severe) that best represents his or her pain intensity level (Jensen & Karoly, 2011).…”
Section: Introductionmentioning
confidence: 99%